(untitled) (World Bulletin of Management and Law, 2024)
The aim of the study was to compare the effect of pomegranate seed oil on the morphofunctional state of the gastric mucosa in rats with experimental "indomethacin" ulcer. Materials and methods: The ulcerative lesion was modeled by intragastric administration of indomethacin, the studied drugs were administered preemptively daily for seven days. The condition of the mucosa was assessed macro-and microscopically. Results and conclusions: Pomegranate seed oil has a pronounced gastroprotective effect, which is manifested in a decrease in the number and depth of coolant erosions, a decrease in the Pauls index for banded erosions, and an increase in mucosal thickness.